Byaṅ gter Rdzogs chen Dgoṅs pa zaṅ thal and Thugs sgrub skor : collections of texts from two cycles of rediscovered teachings of the Byaṅ-gter or Rdo-rje-brag tradition of the Rñiṅ-ma-pa school - Rgod-kyi-ldem-ʼphru-can, Gter-ston, 1337-1408 (Orgyan Dorji, 1978)
Dzogchen teachings and precepts of the Changter tradition of the Nyingmapa sect.